A Dynamic Evaluation Method for High-Permeability New Energy Distribution Network Planning Considering Multistage Development Trends - Zhang, Junxiao; Gao, Chong; Wang, Tianlin; Duan, Yao; Xu, Min; Guo, Zuogang (Frontiers in Energy Research, 2022)
With the development of the new power system, high penetration of new energy (HPNE) will become a major feature of power system in the future. In order to solve the problem that the traditional distribution network planning index is difficult to fully consider the impact of new energy access on the distribution network, this paper constructs a distribution network planning evaluation index system considering the characteristics of HPNE, and designs a static comprehensive evaluation method of distribution network planning scheme based on "over-average penalty" entropy weight method. At the same time, distribution network planning is a long-term dynamic process, and the static evaluation method is difficult to describe the actual situation of the multi-stage construction process of distribution network. To this end, a dynamic evaluation method of distribution network planning is proposed, which realizes the comprehensive evaluation of multi-stage distribution network planning based on the dual excitation control line. Finally, an example of four 10kV distribution network planning schemes of a power supply bureau is analyzed to prove the effectiveness of proposed method.